2018
DOI: 10.1093/oep/gpy058
|View full text |Cite
|
Sign up to set email alerts
|

Social capital as an instrument for common pool resource management: a case study of irrigation management in Sri Lanka

Abstract: Although social capital is considered to be a key instrument for common pool resource (CPR) management, its effect among heterogenous players such as upstream and downstream farmers along an irrigation canal is not clear. Using a combination of lab-in-the-field experiments to measure social capital and household survey data in a unique natural experimental setting, this study shows that upstream farmers with higher trust toward the downstream farmers are more likely to be satisfied with their water usage. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…Related to network social capital for instance, (Esterhuyse, 2012) proves that social networks are crucial in water management, especially in agriculture in planning and implementing production-increasing initiatives. Meanwhile, research results by (Aida, 2019) show that social capital in the form of trust will encourage the satisfaction of water users. Upstream farmers who trust downstream farmers are more likely to be satisfied with their water use.…”
Section: The Role Of Social Capital In the Circular Economy Of Water ...mentioning
confidence: 99%
“…Related to network social capital for instance, (Esterhuyse, 2012) proves that social networks are crucial in water management, especially in agriculture in planning and implementing production-increasing initiatives. Meanwhile, research results by (Aida, 2019) show that social capital in the form of trust will encourage the satisfaction of water users. Upstream farmers who trust downstream farmers are more likely to be satisfied with their water use.…”
Section: The Role Of Social Capital In the Circular Economy Of Water ...mentioning
confidence: 99%
“…Community work involves various formal and informal activities with respect to both production and non‐production activities in this area. For example, in the irrigated areas each distribution canal community (D‐canal), the second smallest unit of branch canal, has a farmer organization whose objective is to facilitate such activities as problem solving among farmers, maintenance of irrigation facilities and communal roads, collective procurement of farm inputs, cooperative marketing of products, arrangement of loans to farmers, and religious festival preparations (Aida, 2019). All settlers are required to register with the farmer organization and to attend their meetings, although explicit enforcement mechanisms do not exist.…”
Section: Study Site Data Description and Natural Experimentsmentioning
confidence: 99%
“…In contrast, several studies have shown that the tail-end farmers are always exposed to a higher level of risk and uncertainty because they demonstrably receive a smaller share of water compared to the headend farmers (Shantha & Ali, 2013;Pieris et al, 2004). As head-end farmers have immediate access to the source compared to those downstream, they tend to use more than their fair share of water unless water quotas are strictly enforced (Paranage, 2018;Aheeyar et al, 2012;Aida, 2019;Wijerathna, 2005;Pieris et al, 2004). Several studies on irrigation management have pointed out that farmers at the head-end tend to over-irrigate their fields, without considering the tail-end commands, and thereby violate the rules.…”
Section: Inefficiency and Inequity In Irrigation Water Distributionmentioning
confidence: 99%
“…Illegal drawing of water and the resulting disharmony among farmers are the most vexing problems faced by tail-end water users. Apart from conveyance losses and technical constraints, illegal water tapping causes inequity in water distribution, leading to conflicts among farmers (Aida, 2019). Saumyarathna et al (2016) and Aheeyar et al (2012) have pointed out that competition for limited water supplies and conflicts in sharing water among different water users was a common issue faced in the management of the present irrigation system.…”
Section: Inefficiency and Inequity In Irrigation Water Distributionmentioning
confidence: 99%